2015
DOI: 10.1161/circep.115.003272
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Atrial Fibrillation in Patients With Congenital Heart Defects

Abstract: Age at development of AF in patients with CHD is relatively young compared with the patients without CHD. Coexistence of episodes of AF and regular AT occurred in a considerable number of patients; most of them initially presented with regular AT. The fast and frequent progression from paroxysmal to (long-standing) persistent or permanent AF episodes justifies close follow-up and early, aggressive therapy of both AT and AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 42 publications
3
32
1
1
Order By: Relevance
“…In addition to occurring at higher rates, AF also seems to have presented at a much younger age in our cohort. This is consistent with other studies showing relatively young age at development of AF in patients with ACHD [10]. Risk stratification systems such as CHADS 2 [11] and CHADS-VASc [12] have been validated for use in non-valvular AF in the general population, but may not apply to ACHD.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to occurring at higher rates, AF also seems to have presented at a much younger age in our cohort. This is consistent with other studies showing relatively young age at development of AF in patients with ACHD [10]. Risk stratification systems such as CHADS 2 [11] and CHADS-VASc [12] have been validated for use in non-valvular AF in the general population, but may not apply to ACHD.…”
Section: Discussionsupporting
confidence: 85%
“…In more than 60% of the study population, AF coexisted with regular SVT, which is much higher compared to the 33% that was reported in an earlier study with 199 patients with various CHD and AF . This observation suggests that ToF patients are more prone to development of regular SVT compared to patients with other CHD.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies identified palliative shunting prior to total ToF correction as a predictor for SVT and AF . Also, it was suggested that regular SVT might facilitate development of AF in CHD patients …”
Section: Introductionmentioning
confidence: 99%
“…In this study, TGA patients were relatively young at onset of AF compared to patients with several other, less complex CHD 58. It is likely that AF in this patient population is not only the result of aging.…”
mentioning
confidence: 68%
“…It is likely that AF in this patient population is not only the result of aging. Other proarrhythmic factors include the presence of scars, suture lines and11 intra-atrial conduction abnormalities and local dispersion in refractoriness due to chronic hemodynamic stress 22,58. Frankel et al reported outcomes of pulmonary vein isolation in a TGA patient after the Mustard operation who presented with recurrent episodes of AF 22.…”
mentioning
confidence: 99%